EMC of Analog Integrated Circuits - Redouté, Jean-Michel.; Steyaert, Michiel; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Environmental electromagnetic pollution has drastically increased over the last decades. The omnipresence of communication systems, various electronic appliances and the use of ever increasing frequencies, all contribute to a noisy electromagnetic environment which acts detrimentally on sensitive electronic equipment. Integrated circuits must be able to operate satisfactorily while cohabiting harmoniously in the same appliance, and not generate intolerable levels of electromagnetic emission, while maintaining a sound immunity to potential electromagnetic disturbances: analog integrated circuits are in particular more easily disturbed than their digital counterparts, since they don't have the benefit of dealing with predefined levels ensuring an innate immunity to disturbances. In addition, as different electronic systems are compactly integrated in the same apparatus, the parasitic electromagnetic coupling between these circuits sharing the same signal, power and ground lines, is a critical design parameter that can no longer be safely excluded from a product design flow: as an example, Bluetooth, GSM and WiFi services have to coexist and operate in harmony within the crammed confinement of a modern mobile phone. The objective of the research domain presented in EMC of Analog Integrated Circuits is to improve the electromagnetic immunity of considered analog integrated circuits, so that they start to fail at relevantly higher conduction levels than before.
Basic EMC Concepts at IC Level -- EMC of Integrated Circuits versus Distortion -- EMI Resisting Analog Output Circuits -- EMI Resisting Analog Input Circuits -- EMI Resisting Bandgap References and Low Dropout Voltage Regulators -- Epilogue.
Keywords: Electronic circuits; Electrical engineering; Solid state physics; Spectroscopy; Microscopy; Circuits and Systems; Communications Engineering, Networks; Solid State Physics; Spectroscopy and Microscopy